Prevalence of stunting, wasting and underweight in Grade 1-learners: The NW-CHILD Study - Gizelle Kruger; Anita E. Pienaar; Dané Coetzee; Salomé H. Kruger (AOSIS, 2014)
Background: Child undernutrition remains a major public health concern in developing countries, with many negative consequences to child development. Objectives: To determine the prevalence of stunting, wasting and underweight amongst Grade 1-learners in the North West Province (NWP) of South Africa (SA), taking into account gender, race and school type. Method: Eight hundred and sixteen (419 boys, 397 girls) learners participated in the study (567 black, 218 white, 31 other races). Underweight, stunting and wasting (Weight-for-age, height-for-age, BMI-for-age) were determined using the z-scores of the 2007 WHO reference sample (-2 SD). Results: A higher prevalence of wasting and underweight were found amongst the boys (8.35%; 5.97%) compared with the girls (6.30%; 2.52%), although this was only significant for underweight (p = 0.02), whilst stunting percentages were very similar amongst girls (4.53%) and boys (4.06%). Underweight was the highest in the black group (5.47%; p < 0.01), compared with the white group (0.46%) and the prevalence of the conditions is associated with school types which represent low socio-economic circumstances (Quintile 1-3 schools). Only black learners showed stunting (p < 0.01) and more black learners were wasted (n = 39) compared with white (n = 15; p = 0.08) learners. Quintile 1-3 schools had a significantly higher prevalence of underweight (5.14% - 8.18%) and stunting (3.88% - 10.7%) (p < 0.01) compared with Quintile 4 and 5 schools. Conclusion: The prevalence of stunting, wasting and underweight need improvement amongst school beginners, especially in Quintile 1-3 type schools but also amongst black learners living in the NWP of SA as it can have significant hampering effects on the future development and well-being of children. Agtergrond: Ondervoeding is steeds 'n publieke gesondheidsgevaar by kinders in ontwikklende lande, met heelwat negatiewe gevolge vir kinderontwikkeling.   Doel: Om te bepaal wat die voorkoms van groei-inperking, ondervoeding en ondergewig by Graad 1-leerders in die Noordwes-Provinsie (NWP) van Suid-Afrika (SA) is, met in ag neming van geslag, ras en skooltipe. Metode: Agt honderd en sestien leerders (419 seuns; 397 meisies) is ewekansig geselekteer vir deelname aan die studie (567 swart, 218 wit, 31 ander rasgroepe). Ondergewig, groei-inperking en ondervoeding is bepaal deur z-tellings vir massa-vir-ouderdom, lengte-vir-ouderdom en LMI-vir-ouderdom volgens die 2007 WHO verwysings (-2 SA). Resultate: 'n Hoër voorkoms vir ondervoeding en ondergewig is by seuns (8.35%; 5.97%) teenoor meisies (6.30%; 2.52%) gevind, alhoewel slegs betekenisvol vir ondergewig (p = 0.02), terrwyl persentasies van groei-inperking redelik dieselfde was by meisies (4.53%) en seuns (4.06%). Ondergewig het die hoogste voorkoms in die swart groep (5.47%; p < 0.01) getoon, en die voorkoms word geassosieer met skooltipes wat lae sosio-ekonomiese omstandighede verteenwoordig. Slegs swart leerders het groei-inperking getoon (p < 0.01) en meer swart leerders was ondervoed (n = 39) teenoor blanke (n = 15) leerders. Kwintiel 1-3 skole het 'n betekenisvolle hoër voorkoms vir ondergewig (5.14% - 8.18%) en groei-inperking (3.88% - 10.7%) getoon (p < 0.01) as die Kwintiel 4 en 5 skole. Gevolgtrekking: Groei-inperking, ondervoeding en ondergewig moet by skoolbeginners verbeter word, veral in Kwintiel 1-3 skooltipes en by Swart leerlinge in die NWP van SA, veral weens die negatiewe uitwerking wat dit op die toekomstige ontwikkeling en welstand van leerders wat daaronder gebuk gaan, kan uitoefen.